Unemployed Female Translators in Saudi Arabia: Causes and Solutions - Al-Jarf, Reima (Meta, 1999)
AbstractThe present study found that 90% of female Saudi translators who graduated between 1990 and 1996 are not working as translators. Although translation jobs are available in hospitals, translation bureaus, and embassies, many graduates find the jobs open for women unsuitable because of working conditions, stringent qualifications, staff policies, salaries and benefits. Others disliked the nature of the work and cited insufficient information about employment opportunities, lack of motivation, and familial, social, and cultural factors as reasons for unemployment.